PENGARUH KUALITAS LAYANAN TERHADAP WORD OF MOUTH (WOM) DENGAN KEPUASAN KONSUMEN SEBAGAI MEDIASI (Studi pada Perusahaan Organda (PO) Slamet di Pati) (Students' Journal of Economic and Management, 2014)
Quality of service is one of the key factors for the success of a company as an industry that offers services products. Quality of service can affect customer satisfaction. Customer satisfaction is a significant determinant of repeat purchases, information from positive word of mouth and customer loyalty. Satisfied customer will take action word of mouth (WOM). Word of mouth (WOM) marketing is a business that triggers consumers to discuss, promote, recommend and sell products / brands to other customers. Population in this research is that consumers Organda Company (PO) Slamet, J1. Starch Kingdom - Tayu, KM 3, in Pati. And the sample in this study was 100. The analysis technique used is the Path Analysis. The results showed that: (1). service quality and significant positive effect on customer satisfaction. (2). customer satisfaction and a significant positive effect on word of mouth. (3). affect the quality of service by word of mouth consumer satisfaction as an intervening variable. Keywords : Quality Service, Consumen Satisfaction, Word Of Mouth